2017
DOI: 10.1002/mrm.26907
|View full text |Cite
|
Sign up to set email alerts
|

Whole brain inhomogeneous magnetization transfer (ihMT) imaging: Sensitivity enhancement within a steady‐state gradient echo sequence

Abstract: The proposed sensitivity-boosted and time-efficient steady-state ihMT-gradient echo sequence, implemented and optimized at 1.5T, allowed robust high-resolution 3D ihMT imaging of the whole brain within a clinically compatible scan time. Magn Reson Med 79:2607-2619, 2018. © 2017 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
105
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(127 citation statements)
references
References 30 publications
16
105
2
Order By: Relevance
“…Histological research has revealed that myelination continues throughout adolescence (Benes, ; Yakovlev & Lecours, ), thus it remains possible that MT and ihMT measures applied to date have lacked the sensitivity required to describe myelination during this period. Optimizations to ihMT methods have been identified which may enable future studies to address myelination trajectories during adolescence with greater clarity (McHinda et al, ; Prevost et al, ). When considered together, our VF m and qihMT findings suggest that myelin sheaths may be incorporating more water between a relatively stable number of wrapped membranes during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Histological research has revealed that myelination continues throughout adolescence (Benes, ; Yakovlev & Lecours, ), thus it remains possible that MT and ihMT measures applied to date have lacked the sensitivity required to describe myelination during this period. Optimizations to ihMT methods have been identified which may enable future studies to address myelination trajectories during adolescence with greater clarity (McHinda et al, ; Prevost et al, ). When considered together, our VF m and qihMT findings suggest that myelin sheaths may be incorporating more water between a relatively stable number of wrapped membranes during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that this choice of slice thickness (10 mm) was driven by the important need of SNR in the ihMT acquisition and was applied to DTI to ensure the same PVE‐induced contamination. Current strategies developed to enhance the ihMT signal will greatly help to handle these issues in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…7 T) should be feasible in principle as long as the RF energy deposition is maintained within regulatory constraints. In this perspective, recent strategies aimed at reducing the RF demand to optimize the ihMTR are of great utility …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the healthy population, tissue type distributions resemble those obtained with a state‐of‐the‐art ihMT protocol (see Figure of Mchinda et al) with 2 distinct peaks for WM and cGM, and a higher BPF in the dGM structures, e.g., the thalamus, compared with cGM. The clearer separation between distributions provided by ihMT points toward the higher sensitivity of ihMT to myelin than conventional MT; however, the quantitative nature of the BPF may be advantageous when using such a parameter to quantify changes in disease.…”
Section: Discussionmentioning
confidence: 53%